Identification of incident poisoning, fracture and burn events using linked primary care, secondary care, and mortality data from England: implications for research and surveillance - Baker, Ruth; Tata, Laila J.; Kendrick, Denise; Orton, Elizabeth (BMJ Publishing Group, 2015)
Background: English national injury data collection systems are restricted to hospitalisations and deaths. With recent linkage of a large primary care database, the Clinical Practice Research Datalink (CPRD), with secondary care and mortality data we aimed to assess the utility of linked data for injury research and surveillance by examining recording patterns and comparing incidence of common injuries across data sources. Methods: The incidence of poisonings, fractures and burns was estimated for a cohort of 2,147,853 0-24 year olds using CPRD linked to Hospital Episode Statistics (HES) and Office for National Statistics (ONS) mortality data between 1997-2012. Time-based algorithms were developed to identify incident events, distinguishing between repeat follow-up records for the same injury, and those for a new event. Results: We identified 42,985 poisoning, 185,517 fracture and 36,719 burn events in linked CPRD-HES-ONS data; incidence rates were 41.9 per 10,000 person-years (95% confidence interval 41.4–42.4), 180.8 (179.8–181.7) and 35.8 (35.4–36.1), respectively. Of the injuries, 22,628(53%) poisonings, 139,662(75%) fractures, and 33,462(91%) burns were only recorded within CPRD. Only 16% of deaths from poisoning (n=106) or fracture (n=58) recorded in ONS were recorded within CPRD and/or HES records. None of the 10 deaths from burns were recorded in CPRD or HES records. Conclusion: It is essential to use linked primary care, hospitalisation and deaths data to estimate injury burden, as many injury events are only captured within a single data source. Linked routinely-collected data offer an immediate and affordable mechanism for injury surveillance and analyses of population based injury epidemiology in England.